The value of aggregation in ensuring the economic security of energy companies (Economics and region, 2025)
The study attempts to transfer knowledge on the importance of introducing aggregation in the electricity market for both energy sector enterprises and other market participants. The main technical and economic advantages of introducing an aggregation mechanism are identified. It is emphasised that creating aggregators and aggregated groups allows solving key problems in the electricity sector. This, in particular, contributes to a more efficient balancing of electricity supply and demand, a prerequisite for the stable functioning of energy systems. Additionally, it is noted that aggregation allows for optimising the load on the grid, reducing the risk of overload and increasing the efficiency of the use of generated resources. In addition, aggregated groups can use modern technologies for monitoring and forecasting consumption, which allows them to respond quickly to market changes and increase the level of adaptability of energy companies. Particular attention is paid to the impact of hostile attacks on Ukraine's energy sector. The large-scale invasion of Russian troops led to significant losses of energy companies due to targeted attacks on critical infrastructure, which caused interruptions in electricity supply and complicated the functioning of the country's economy. In this context, the need for new approaches to managing electricity generation and consumption, improving pricing mechanisms and developing small-scale generation, which will help strengthen the country's energy security, is substantiated. Another important aspect is stimulating investment in decentralised energy sources, which will help increase energy independence and market flexibility. Using renewable sources in aggregated groups will reduce dependence on traditional energy sources and contribute to the environmental sustainability of the energy sector. At the same time, aggregation will balance electricity production and consumption, regulate its sale and purchase in the relevant market, and thus, to some extent, guarantee the economic security of energy companies.
Keywords: economic security of energy enterprises; economic losses; guaranteeing economic security; aggregation; aggregator; aggregated group; electricity balancing; market price for electricity; additional income